Veterans Crisis Hotline - Chopan, Jon (Book collections on Project MUSE., 2018)
"The twelve stories of Veterans Crisis Hotline offer a meditation on the relationship between war and righteousness and consider the impossible distance between who men are and who they want to be. A veteran working at the hotline listens to the stories men tell when they need someone to hear their voices, when they need to access a language for their pain. Two men search for the head of a decapitated Iraqi civilian so that they might absolve themselves of the atrocities of war, a Marine hunts for the man who raped his girlfriend, and a teenage son replaces his dead father on the battlefield. With a quick wit and offbeat humor, Jon Chopan takes us from the banks of the Euphrates to the bars and VFW halls of the Rust Belt, providing insight into the Iraq War and its enduring impact on those who volunteered to fight in it"--